Gioulika-Olga Christakopoulou, To Die in Style! The Residential Lifestyle of Feasting and Dying in Iron Age Stamna, Greece - Bintliff, John (Journal of Greek Archaeology, 2021)
This short essay presents some of the most interesting information from a major Early Iron Age cemetery in the province of Aetolia, in North-West Mainland Greece. Its presentation is rather uneven – the location of the site is not even immediately presented in the opening text, and there is no overall plan of the site – although the content is important enough to make it worth the effort. Over 600 tombs of the earliest Iron Age, the Protogeometric (PG) era (ca. 1050-900 BC), have so far been uncovered in a burial zone some 4km in length along the periphery of Lake Aetolikon, both cremations and inhumations. Several tombs appear to belong to elite ‘warrior’ males, indicating a ranked society.